A Sociolinguistic Study of Code-Switching in the Algerian Hirak "Movement" - Agti, Abdelaziz (جامعة الجلفة, 2022)
لا يمكن فصل ظاهرة التناوب اللغوي عن حقيقة أن العديد من الأشخاص هم ثنائي اللغة وثلاثي اللغة وحتى متعددي اللغات. لقد أصبح التناوب اللغوي اجتماعيا وتواصليا لا مفر منه. تهدف هذه الدراسة إلى معرفة الأسباب والدوافع الكامنة وراء استخدام التناوب اللغوي في الشعارات التي يحملها المتظاهرون في الحراك في الجزائر. يتم جمع بيانات الدراسة الحالية من الحراك وتحليلها باستخدام المنهج النوعي الوصفي لتحديد العوامل الاجتماعية والثقافية التي يقوم عليها التناوب اللغوي. توضح النتائج أن المتغيرات الاجتماعية والثقافية هي عوامل قوية في تحديد استخدام التناوب اللغوي. إن نوع التناوب اللغوي المستخدم في الحراك والمهيمن هو التناوب بين الجمل. Code-switching phenomenon cannot be separated from the fact that many people are bilingual, trilingual and even multilingual. Code switching has become socially and communicatively unavoidable. The main focus of our study is to find out the reasons and motivations behind using code-switching in the slogans carried by the demonstrators in the hirak in Algeria. Data for the present study are collected from the hirak and analyzed, using descriptive qualitative method to identify socio-cultural factors that underlie code switching. The results reveal that socio-cultural variables appear to be strong factors in determining the use of code-switching. The most dominant type of code-switching used in the hirak is inter-sentential switching.
Keywords: علم اللغة الاجتماعي -- التعددية اللغوية -- التداخل اللفظي -- الحراك الاجتماعي -- الثقافة الجزائرية -- العلاقات الاجتماعية